Biotic responses buffer warming‐induced soil organic carbon loss in Arctic tundra. (12th June 2018) - Liang, Junyi; Xia, Jiangyang; Shi, Zheng; Jiang, Lifen; Ma, Shuang; Lu, Xingjie; Mauritz, Marguerite; Natali, Susan M.; Pegoraro, Elaine; Penton, Christopher Ryan; Plaza, César; Salmon, Verity G.; et al.
Abstract: Climate warming can result in both abiotic (e.g., permafrost thaw) and biotic (e.g., microbial functional genes) changes in Arctic tundra. Recent research has incorporated dynamic permafrost thaw in Earth system models (ESMs) and indicates that Arctic tundra could be a significant future carbon (C) source due to the enhanced decomposition of thawed deep soil C. However, warming‐induced biotic changes may influence biologically related parameters and the consequent projections in ESMs. How model parameters associated with biotic responses will change under warming and to what extent these changes affect projected C budgets have not been carefully examined. In this study, we synthesized six data sets over 5 years from a soil warming experiment at the Eight Mile Lake, Alaska, into the Terrestrial ECOsystem (TECO) model with a probabilistic inversion approach. The TECO model used multiple soil layers to track dynamics of thawed soil under different treatments. Our results show that warming increased light use efficiency of vegetation photosynthesis but decreased baseline (i.e., environment‐corrected) turnover rates of SOC in both the fast and slow pools in comparison with those under control. Moreover, the parameter changes generally amplified over time, suggesting processes of gradual physiological acclimation and functional gene shifts of both plants and microbes. The TECO model predicted that field warming from 2009 to 2013 resulted in cumulative C losses of 224 or 87 g/m 2, respectively, without or with changes in those parameters. Thus, warming‐induced parameter changes reduced predicted soil C loss by 61%. Our study suggests that it is critical to incorporate biotic changes in ESMs to improve the model performance in predicting C dynamics in permafrost regions. Abstract : Ecosystem models usually use scenario‐invariant constants as parameters to represent processes at multiple scales. However, warming‐induced biotic changes may influence biologically related parameters and the consequent projections in models. This study showed that warming increased light use efficiency of plant carbon assimilation, and decreased baseline (i.e., environment‐corrected) turnover rates of fast and slow soil carbon pools, resulting in a significant reduction of soil carbon emission to the atmosphere in an Arctic tundra. This study suggests that it is critical to incorporate biotic changes in ecosystem models to improve the model performance in predicting carbon dynamics.